Luces y sombras del Río Tinto (Huelva): el ciclo integral del agua y nuevos horizontes - Jurado Almonte, José Manuel (M+A. Revista Electrónica de Medioambiente, 2010)
Our intention is to amplify the knowledge about the integral water cycle over the Tinto River Basin towns. In this context, some physic and historical features are covered, and by extension, other water resources of the province of Huelva. At the same time, the paper reflects on the water mancomunities role and on the increased water demands from agriculture. The shadows of this river are its pollution problems (mines in its headwater and chemical industries in its mouth) and the new hopes are conduced by its new environmental interest, the plans of correction and the tourist possibilities of this territory. Also, we must pay attention on the institutional, legislative and territorial framework scales, from Andalusia to the European Union. Precisely, Water Framework Directive 2000 comes from EU. It has activated profound conceptual water normative and institutional changes in Spain and Andalusia.